2016
DOI: 10.1371/journal.pone.0166740
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Alleviates Experimental Diabetic Cardiomyopathy by Regulating the GSK-3β-PP2Ac-NF-κB Signaling Axis

Abstract: Recent studies reported that atorvastatin (ATOR) alleviated progression of experimental diabetic cardiomyopathy (DCM), possibly by protecting against apoptosis. However, the underlying mechanisms of this protective effect remain unclear. Therefore, our study investigated the role of the glycogen synthase kinase (GSK)-3β-protein phosphatase 2A(PP2A)-NF-κB signaling pathway in the anti-apoptotic and cardioprotective effects of ATOR on cardiomyocytes cultured in high glucose (HG) and in DCM. Our results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…These indicated that interstitial collagen deposition, ERS-related apoptosis, and NF- κ B-mediated inflammation were induced in diabetic ApoE −/− mice. Consistent with the results of previous studies [ 15 , 16 , 19 , 24 ], atorvastatin treatment improved the histological abnormalities, fibrosis, and apoptosis of cardiomyocytes via inhibition of NF- κ B-induced inflammation and cleaved caspase-3-mediated apoptosis in the diabetic heart. To our knowledge, the present study is the first study to show that traditional Chinese medicine, GBE, could protect against diabetic myocardial injury, particularly apoptosis, myocardial fibrosis, and NF- κ B-mediated inflammation via inhibition of ERS-related apoptosis, as evidenced by the decrease in p-JNK, caspase-12, and cleaved caspase-3 expression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These indicated that interstitial collagen deposition, ERS-related apoptosis, and NF- κ B-mediated inflammation were induced in diabetic ApoE −/− mice. Consistent with the results of previous studies [ 15 , 16 , 19 , 24 ], atorvastatin treatment improved the histological abnormalities, fibrosis, and apoptosis of cardiomyocytes via inhibition of NF- κ B-induced inflammation and cleaved caspase-3-mediated apoptosis in the diabetic heart. To our knowledge, the present study is the first study to show that traditional Chinese medicine, GBE, could protect against diabetic myocardial injury, particularly apoptosis, myocardial fibrosis, and NF- κ B-mediated inflammation via inhibition of ERS-related apoptosis, as evidenced by the decrease in p-JNK, caspase-12, and cleaved caspase-3 expression.…”
Section: Discussionsupporting
confidence: 91%
“…Mice exhibiting plasma glucose levels > 12 mmol/L were considered diabetic and were used in the study ( n = 58) [ 13 , 14 ]. The diabetic mice were then treated with atorvastatin [ 15 , 16 ] (10 mg/kg/day, intragastric (i.g. ), n = 14), GBE at a low dose (200 mg/kg/day, i.g., n = 16), or GBE at a high dose (400 mg/kg/day, i.g., n = 17).…”
Section: Methodsmentioning
confidence: 99%
“…Thomas et al [ 31 ] demonstrated that cardiomyocyte-specific NF- κ B signaling inhibition could attenuate diabetes-induced cardiac dysfunction through the suppression of the cardiac renin-angiotensin system. Interestingly, several anti-inflammatory compounds, such as atorvastatin [ 32 , 33 ] and cannabidiol [ 13 ], were found to be beneficial for the treatment of DCM. Consistent with previous studies [ 15 , 22 ], our results indicated that Andro treatment effectively suppressed NF- κ B activation and the expression of inflammatory cytokines, along with the subsequent decreased myocardial damage in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is a key transcription factor regulating inflammatory responses and the expression of hyperglycemic stress related immediate early genes (35). Previous studies showed that NF-κB regulated several signal transduction pathways in cardiomyocytes under stimulation with HG (36,37). Hence, blocking NF-κB might attenuate HG-induced cardiac hypertrophy (38) in cardiac hypertrophy models.…”
Section: Discussionmentioning
confidence: 99%